Conceptualising mentorship pedagogy on entrepreneurship intention / Suhailah Kassim ... [et al.] - Kassim, Suhailah; Ahmad Fadzil, Ahmad Syahmi; Ibrahim, Khalilah; Mohamed, Noor Azzura; Wan Mohamed, Nik Rozilani (UiTM Press, 2024)
This study uses the Theory of Planned Behaviour (TPB) to evaluate how mentorship pedagogy affects student entrepreneurial intention. This study explores how mentorship affects HLIs students, focusing on its impact on entrepreneurial mindsets, the complex relationship between mentorship and entrepreneurial ambition can be examined using Theory of Planned Behaviour (TPB) which includes attitudes, subjective norms and perceived behaviour control, Higher education students will be the samples for this study. Mentorship pedagogy is used to determine how it affects students’ attitudes towards entrepreneurship. The study also explores how mentorship develops subjective norms through social interactions and normative beliefs and increases perceived behavioural control by providing students with skills, resources and a supportive environment. The purpose of this conceptual paper is to understand how educators as mentors can influence student’s entrepreneurial intention using TPB as a guiding model. The purpose of this conceptual paper is to foster student ambitions towards becoming entrepreneurs. This study also contributes to the ongoing conversation on improving student’s entrepreneurship intention.